Evaluating bio-physicochemical properties of raw powder prepared from whole larvae containing liquid silk of the domestic silkworm - Hashimoto, Shusuke; Yamazaki, Maki; Uehara, Hiroshi; Yamazaki, Shinya; Kobayashi, Masakazu; Yokoyama, Takeshi; Yazawa, Kenjiro; Shiomi, Kunihiro (Frontiers in Nutrition, 2024)
The domestic silkworm, Bombyx mori, has been widely used in silk production for centuries. It is also used as a bioreactor by the textile and pharmaceutical industries to mass produce recombinant bioactive proteins containing silk-based materials. Furthermore, silkworms are well-known as a source of food and have also been orally administered to prevent and treat several human disorders. In this study, we aimed to investigate the inherent bio-physicochemical properties of edible silkworms to accurately evaluate their clinical and nutritional potential. We prepared raw powder from whole larvae of silkworm. The yield rate of the powder derived from dried larvae was almost 100% (98.1–99.1% in replicates). As “percentage yield” translates to “Budomari” in Japanese, this raw powder was named “B100rw”. We further prepared B100dn that was denatured through autoclaving. Thereafter, we examined whether B100rw sustained the original bio-physicochemical properties by comparing it with B100dn. There was no significant difference in nutritional content between B100rw and B100dn. B100rw contained proteins derived from silkworm larvae and mulberry leaves, whereas the proteins of B100dn were mostly degraded. On measuring the enzymatic activity of both powders using trehalase as an indicator enzyme, B100rw was found to maintain trehalase activity. B100rw also maintained a random coil conformation, similar to that of liquid silk. This suggested that B100rw sustained the unique bio-physicochemical properties of living larvae. These findings may facilitate the development of novel food products or orally administered vaccines.